Ensuring Regional Security is the Main Criterion of the Foreign Policy of Uzbekistan - Kuyliev, Tulkin (European Journal of Life Safety and Stability (2660-9630), 2022)
This article analyzes the role of ensuring a transparent process of stability and improvement of international relations in foreign policy. It also considers an analysis of some of the arguments that have been important in our State since the first days of Independence and especially today, the difficult period of the task of ensuring peace and tranquility, the development of military power, the process of fulfilling priority tasks in the field of foreign policy.